Nutritional Composition, Bioactive Components and Antioxidant Activity of Garden Cress (Lepidium sativum L.) Grown Under Deficit Irrigation - Yildirim, Ertan; Ekinci, Melek; Turan, Metin; Goktas, Hamza; Budak, Derya Nil; Sagdic, Osman (MDPI, 2025)
This study examined how different water restriction levels (T100%, T85%, T75%, and T55%) influence the nutritional and bioactive compounds of Bahar and Dada & scedil; cress (Lepidium sativum L.) cultivars. The highest levels of phenolic compounds found in Dada & scedil; and Bahar cress were quercetin (8.33 +/- 0.23-9.32 +/- 0.25 mu g/L), ferulic acid (8.08 +/- 0.18-8.42 +/- 0.19 mu g/L), catechin (6.83 +/- 0.28 mu g/L), and caftaric acid (5.40 +/- 0.45 mu g/L). Mild and moderate drought treatments (85% and 75% humidity) caused notable increases in phenolic compounds. The highest antioxidant enzyme levels were observed as GST, 6GPD, and G6PD in Bahar and Dada & scedil; cress, with enzyme levels rising under drought conditions. Notably, the mild drought treatment roughly doubled peonidin-3-glucoside acetyl levels in the cress cultivars. Sugar contents of Dada & scedil; and Bahar cress cultivars also rose significantly with drought treatment. Riboflavin, the most abundant vitamin in cress cultivars, increased to 40.96 +/- 1.24 mg/kg in Dada & scedil; and 30.79 +/- 1.60 mg/kg in Bahar cress under drought stress. Amino acids showed the highest increases under severe drought, with asparagine rising by roughly 2.76-fold and leucine increasing by 2.67-fold in Bahar cress. These findings suggest that controlled water restriction can enhance the nutritional and bioactive properties of cress, potentially leading to more nutrient-rich products for the food industry and human health.
Keywords: drought stress; garden cress; phenolic compounds; antioxidant enzymes; nutritional compounds; anthocyanins; VITIS-VINIFERA L.; PLANTS; RESPONSES; LEAVES; ACCUMULATION; METABOLISM; TOLERANCE; QUALITY; IMPACT; Agriculture